Where and Why Immigrants Intend to Naturalize: The Interplay Between Acculturation Strategies and Integration Policies - Politi, Emanuele; Bennour, Salomon; Lüders, Adrian; Manatschal, Anita; Green, Eva G.T. (My University, 2021)
Via naturalization procedures, immigrants have the opportunity to acquire rights and duties limited to nationals. Yet little is known about acculturative contexts and naturalization motives underlying immigrants' naturalization intentions. Employing a large sample of first-generation immigrants in Switzerland (N = 3928) and a multilevel approach, we articulated individual acculturation strategies and cantonal integration policies to explain naturalization intentions and underlying motives. Results at the individual level showed that assimilated immigrants report the highest intentions to naturalize, followed by integrated, and lastly by separated immigrants. Motives underlying naturalization intentions also differed as a function of acculturation strategies. Whereas integrated and assimilated immigrants reported higher symbolic motives than separated immigrants, the latter reported the highest level of instrumental motives. A cross-level interaction qualified results at the individual level. Indeed, the gap between integrated and separated immigrants was more pronounced under inclusive integration policies. Accordingly, integrated immigrants' naturalization intentions increased the more integration policies were inclusive, whereas this was not the case among assimilated and separated immigrants. Overall, our findings cast a positive light on inclusive integration policies as contextual affordances to overcome barriers to naturalization and encourage migration scholars to consider the broader political context in which immigrant acculturation is embedded.